The Harris's honored on their 50th (Raton Range Raton, New Mexico, 1984)
Newspaper Article on the 50th Anniversary of Mr. and Mrs Harold Harris.
Master list item #: 63
File location is in the Raton File Cabinet
Keywords: Harris, Harold; Harris, Tom; Harris, (Mrs.); Welling, Dick; Welling, Mary Ann; Harris, Jerry; Harris, (Mrs.); Harris, Vickie; Harris, Joyce; Palomino, Karry; Couch, Katherine; Barnett, Grace; Harris, Allen; Harris, Howard; Harris, Marjorie; Hendrickson, Dick; Hendrickson, (Mrs.); Boyer, Marjorie; Robinson, Doug; Robinson, Carleen; First United Presbyterian Church; Local History; Biography; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Chula Vista, California; Colorado Springs, Colorado; Las Animas, Colorado; Tulsa, Oklahoma; Cheyenne, Wyoming; Salt Lake City, Utah; Santa Maria, California